الابتكار في الإستراتيجية الإعلانية وأهميتها في جذب انتباه للمستهلك بالإشارة إلى مؤسسة اتصالات الجزائر – المتطلبات والتوصيات- - أ.بارك, نعيمة (Recherches économiques et managériales, 2011)
في ظل التطور الهائل لوسائل التكنولوجيا ، ونتيجة لأهمية استخدام الإعلان عبر وسائل الاتصال الحديثة، فإن المعلنين طوروه وسخروه لتحقيق أهدافهم لإيصال الرسالة الإعلانية المبتكرة للمستهلكين، لذا أصبح لزاما على المؤسسة أن تتبنى إستراتيجية إعلانية ابتكارية فعالة ،نظرا للدور الذي تلعبه هذه الأخيرة في جذب انتباه المستهلكين وترقية مبيعات المؤسسة وخلق مكانة تنافسية لها،ولما كان انفصالها عن قطاع البريد المواصلات ،أصبح لزاما على مؤسسة اتصالات الجزائر أن تعرف بنفسها وخدماتها الجديدة قصد بناء صورة ذهنية لدى المستهلك الجزائري وجذب انتباهه وبالتالي مواجهة منافسيها الخواص في سوق الاتصالات الجزائرية، ولعل أفضل الوسائل لذلك هو الابتكار في الإعلان. Abstract  :   With the enormous development of the means of technology, as a result of the importance of the use of advertising and modern means of communication, the advertisers had manufactured to achieve their goals of getting the message creative advertising to consumers, so it became necessary for the institution to adopt a strategy of advertising innovative and effective, given the role played by the latter to attract the attention of consumers and promote sales the institution and create a competitive position it, and when he was separated from the postal sector of transportation, has become imperative for the institution Algeria Telecom to know themselves and new services in order to build a mental image of the consumer Algerian and attract attention and therefore the face of its competitors properties in the telecommunications market of Algeria, and perhaps the best means for that is innovative in the declaration الكلمات المفتاحية: الابتكار، الإستراتيجية الإعلانية، سلوك المستهلك، جذب الانتباه.